Interaction of working knives of staking machine with leather fabric of fur semi-finished product - Amanov, Auezhan T.; Bahadirov, Gayrat A.; Nabiev, Ayder M.; Khusanov, Kahramanjon; Tsoy, Gerasim N. (Edelweiss Applied Science and Technology, 2025)
The article is devoted to improving the design of a drum machine for staking and cleaning the leather fabric of fur semi-finished products. Additional rollers are added to the pressing device of the machine, which improve the oriented feed of the semi-finished product to the processing drum. The screw roller ensures staking of the semi-finished product with some stretching and, therefore, an increase in the useful area of the finished product is achieved. The interaction of improved knives with the leather fabric of a semi-finished fur product is theoretically considered. The technological process of staking the leather fabric of a fur semi-finished product is theoretically studied. It is determined that when processing a semi-finished product with small protrusions of the wave-shaped blades of the knives, an increase in the relative energy spent on deformation of the leather fabric is achieved. Consequently, it is possible to reduce the costs spent on the force of the pressing device and the velocity of the staking drum, thus improving the working conditions of the personnel servicing the machine.